Intestinal hypoperfusion in patients with Crohn's disease revealed by intraoperative indocyanine green fluorescence imaging. (June 2021) - Higashijima, Jun; Kono, Toru; Shimada, Mitsuo; Kashihara, Hideya; Takasu, Chie; Nishi, Masaaki; Tokunaga, Takuya; Sugitani, Ayumu; Yoshikawa, Kozo
Abstract: Background: Anastomotic leakage has been reported as an independent risk factor for surgical recurrence at the anastomotic site in patients with Crohn's disease. An inadequate blood supply may contribute to this leakage. Real-time indocyanine green angiography has been useful for confirming vascular perfusion of the intestines. The aim of this study was to evaluate the use of intraoperative indocyanine green angiography to detect vascular perfusion of the intestines during ileocaecal resection in patients with Crohn's disease and colon cancer. Materials and methods: We retrospectively evaluated the medical records of 26 consecutive patients with colon cancer arising in the caecum or ascending colon and 3 consecutive patients with Crohn's disease without a history of disease-related surgery. The patients in the 2 cohorts had undergone ileocaecal resection at Tokushima University Hospital between January 2018 and January 2021. After ileocaecal resection, blood flow was evaluated in ileal (oral) and colon (anal) stapled stumps by indocyanine green fluorescence angiography. The fluorescence time was defined as the time from indocyanine green injection and flush of the injection route to the point when the stump showed the strongest fluorescent signal in the monitor. Results: The fluorescence time for the ileal and colon stumps in patients with Crohn's disease was 43.3 ± 8.8 s each and was significantly longer than the fluorescence time in the patients with colon cancer (29.4 ± 6.5 s and 29.6 ± 6.8 s, respectively) (P < 0.05). Conclusion: Intraoperative indocyanine green fluorescence imaging is safe and reproducible for assessing intestinal perfusion prior to anastomosis in patients with colon cancer and Crohn's disease. Highlights: Low blood supply increases leakage and surgical recurrence in Crohn's disease. Indocyanine green angiography is useful for evaluating the intestinal blood supply. Blood supply at anastomotic sites was lower in Crohn's disease than colon cancer.